Die begrippe openbare beleid en openbare belang as kriterium vir kontraktuele geregtigheid - Du Plessis, Stephanus Johannes (North-West University, 1999)
The concepts public policy and public interest often obtain an imprecise content as a criterion for contractual justice in South African law. The consequence of this is some degree of legal uncertainty. This is the problem raised in the present dissertation. From the cases and literature the causes of the problem became clearer and it became evident that the correct basis to deal with this problem is the systematisation of this sphere of the law of contract, which also implies the circumspect dealing with concepts. This was confirmed by the examination of a number of foreign legal systems. It appeared moreover that in these systems too, general criteria are used to evaluate contractual justice, namely: in German law the concepts gute Sitten and Treu und Glauben, in Dutch law the concepts goede zeden, openbare orde, as well as redelijkheid en billijkheid (goede trouw) and in English law the concept public policy and possibly in future also the concept good faith. The foreign systems furthermore provided some solutions regarding the practical implementation of the systematisation. The proposed systematisation firstly implies that public policy and public interest should be understood correctly as a general criterion in this sphere, which means that it has a normative character as well as a flexible nature, which necessarily causes some degree of legal uncertainty. It also implies that public policy and public interest - correctly orientated - should be seen as pivotal to one of the requirements for a valid contract, which is traditionally known as the requirement of legality, but which probably should rather be known as the requirement of lawfulness. This requirement should in addition be understood in a broad sense as also relating to the effect of contracts, and consequently to contractual justice, seen as the relative balance between the interests of the parties. The systematisation furthermore includes the understanding that in this sphere a judge has a limited discretion in exercising a law-creating power. The discretion is limited, especially to prevent a judge from reaching a decision on account of a purely subjective opinion. Regarding this limited discretion an established system of guidelines currently does not exist in South African law, but in the present dissertation a step in this direction was made. The gist of these guidelines is that the nature and the context of the relevant contract or contract term should be observed. The individual case should, however, not be over-emphasised, since that may lead to a superabundance of legal uncertainty and to the misuse of public policy and public interest as a defence. Regarding practical application the systematisation includes in short that various facets of public policy and public interest are distinguished, namely legislation and common law, established views and customs (boni mores), and thirdly public policy and public interest as such, concretised by the concept good faith as the underlying principle. It is submitted that the proposed systematisation could contribute to decreasing the imprecise use of the concepts public policy and public interest and concomitant legal uncertainty.

Restraint of trade at common law - Dempster, Hamish Leslie (University of Auckland, 1997)
This is a collection of essays about the restraint of trade doctrine as laid down in the courts of the United Kingdom and the British Commonwealth. Generally, I will not give an account of the restraint of trade doctrine in the United States of America, for even although each individual state (apart from the civil jurisdictions California and Louisiana) and the federation itself, has a common law system, for reasons peculiar to those jurisdictions, the restraint of trade case law there has become so vast and so confused as to be unsuitable for my purposes. More importantly, however, the common law restraint of trade doctrine in the United Kingdom and the British Commonwealth has been laid down by courts without any significant consideration of the state of the law in the United States. Davies v Davies (1887) 36 Ch D 359, 370 by contrast, the period during which the Privy Council operated as a supra national court of final appeal has resulted in considerable harmony in the doctrine within the British Commonwealth. Even now the House of Lords is influential in Australia and Canada and the influence is increasingly reciprocal. By way of an exception I will discuss the purposes of the anti-trust legislation in the United States. This is necessary because I intend to show that the common law restraint of trade doctrine was not able to be, and was never intended to be, a means of regulating the economy in contradistinction to the United States anti-trust legislation and related legislation in the British Commonwealth. This account is not merely a description of the law relating to the restraint of trade doctrine although I do purport to describe the law. There are other accounts of the restraint of trade doctrine which do that well. Accounts of the restraint of trade doctrine include: Matthews & Adler, The Law Relating to Covenants in Restraints of Trade (London, 2nd ed 1907); Sanderson, Restraint of Trade in English law (London, 1926); Heydon, The Restraint of Trade Doctrine (London, 1971); Trebilcock, The Common Law of Restraint of Trade; A Legal and Economic Analysis (Toronto, 1986); Dean, The Law of Trade Secrets (Sydney, 1990); Mehigan & Griffiths, Restraint of Trade and Business Secrets: Law & Practice (London, 2nd ed 1991); Holdsworth, History of English Law IV (3rd ed, 1945) 343-54, 373-9; VIII (2nd ed, 1937) 56-42. There are other, less detailed accounts in contract law textbooks. The purpose of this dissertation is to describe aspects of the doctrine as it developed between the medieval period and the twentieth century and then to use that account as a basis for an analysis of how the law has taken a number of paths during the twentieth century which cannot be justified by the rules and their justifications which existed in the law prior to that time. Such a development has had important consequences for the restraint of trade doctrine and even the law in general, most of which have been detrimental. I do not intend to give a continuous historical narrative covering the whole of the doctrine. The history has been described before. For example, I do not intend to give a discrete account of the process by which the absolute rule against general restraints of trade gave way to the rule of reason, although I do mention this process where relevant for other purposes. The history, so far as it is relevant, is integrated into each chapter. I will argue that historically the restraint of trade doctrine was a rule or complex of rules, of a certain form and content. The form and content of the rule are important because they bear on the meaning of the class term "restraint of trade" which is an element of the rule. The meaning of that term began to change around the year 1890. Beginning first with certain classes of trade combination, courts began to classify as restraints of trade covenants which did not in fact restrain trade. Then the courts similarly treated the exclusive dealing contract and certain forms of property transaction. Another trend in the law which added to the confusion about the meaning of restraint of trade was the failure by the courts to make definitive findings one way or another as to whether a particular covenant was in restraint of trade. The courts were then faced with a dilemma. The law required a court to refuse to enforce a covenant in restraint of trade unless the covenantee could justify the restraint by presenting evidence to the court from which the courts could assess whether or not that particular restraint was within the reason for the restraint of trade doctrine or not. Such considerations were entirely inapt in the case of covenants which, in accordance with the traditional view, did not restrain trade. Yet if the courts did not validate these contracts, catastrophic consequences would have followed for the parties to such contracts and, indeed, to contract as an institution. To solve the dilemma the courts began to interpret the famous statement of the restraint of trade doctrine by Lord Macnaghten in Nordenfelt v Maxim Nordenfelt Guns & Ammunition Co [1894] AC 535, 565 (HL) literally, rather than contextually. Ultimately this has resulted in the obscuring of the rule underlying the restraint of trade doctrine itself. There were many minor confusions along the way. It is important that the doctrine is coherent and its use consistent with its justifications because it is still a fruitful cause of legal change. In the last year the force of the rule has caused a radical restructuring of Association Football in Europe Bosman’s case. The rule has even penetrated the collective consciousness of the community at large. The broad thrust of the development and the detail will be outlined in the next thirteen chapters.

A behavioural study of the rental housing market in Ibadan, Oyo State of Nigeria - Asaju, Adebakin Simeon (Obafemi Awolowo University, 1994)
Keywords: Besoins en logement; Composition du ménage; Household composition; Housing market; Housing needs; Ibadan; Logement locatif; Marché du logement; Nigeria; Oyo State; Rental housing; État d'Oyo

L'acquisition à crédit des biens d'équipement personnel en droit ivoirien - Kassia, Bi Oula (Université de Nice Sophia-Antipolis, 1993)
L'étude porte sur les techniques juridiques que permettent à un particulier d'acquérir à crédit des biens durables pour son usage personnel ces techniques sont étudiées en relation avec les biens dont elles financent l'acquisition. L'analyse des différentes techniques (première partie), met en lumière l'insuffisance des règles légales et jurisprudentielles régissant la matière. Les rapports des parties sont réglés par les clauses des contrats types. Ceux-ci privilégient la protection du créditeur. Le crédit exerce une influence sur l'ensemble de l'opération d'acquisition (deuxième partie). A cet égard, l'étude du crédit affecte (crédit-bail, prêt lié), permet de constater l'indépendance du contrat de financement et du contrat d'acquisition. Néanmoins, l'acquéreur insatisfait (défaut de délivrance), trouve dans le droit commun un moyen de se protéger : responsabilité, théorie de l'apparence.
Keywords: Achat; Automobiles; Crédit à la consommation; Crédit-bail; Équipement industriel

Genel işlem şartları ve içerik sınırları - Oğuz, Cemal (Ankara Üniversitesi, 1993)
AGB sind vor ihrer Einbeziehung in Einzelvertrâge rechtlich irrelevant. Unser geltendes Recht kennt keine Befugnis zur überindividuellen Gestaltung von Vertragsbedingungen. Man kann die AGB weder Quasi Normen noch iiberindividuelle Besttimungen gualifiziert werden. Im Verhaltnis zu den Individuellvereinbarungen sind sie zweitrangig. Wir haben auch festgestellt dass, die Geltung der AGB für einzelne Vertragsverhâltnisse auf rechtsgeschâftlicher Grundlage beruht und durch das Prinzip der Vertrags freiheit gedeckt wird. Indessen setzt Einbeziehung von AGB in Individialvertrâge eine Einbeziehungsvereinbarung vor. İm Vierten Teil der These haben wir dargestellt dass, die Einbezilhungsvereinbarung inhaltnich auf die Ausgestaltung der Individualabreden beschrânkt. Nur diejenigen Klauseln werden von der Einbeziehungsvereinbarung erfasst, die im Einklang mit den Individuelabreden Stehen. In AGB euthaltene Schriftformklauseln können den mündlichen getroffen Vereinbarung der Parteien die Rechtswirksamkeit nicht nehmen. Werden einzelne Klauseln nicht zum Inhalt von den Parteien abgeschlossenen Individualvertrages, ergibt sich dies aus einer Auslegung der Einbeziehungsvereibarung. Das Problem der Teilnichtigkeit stellt sich nicht. - Lâsst eine Klauseln bei Vernünftiğer Auslegung mindestens zwei Deutungen zu, liegt eine Objektive Unklarheit der AGB vor. Der artige Unklarheiten gehen zu Lasten desjenigen, der die Einführung der AGB in125 den vertrag veranlasst hat. Man muss die dem Kunden günstigere Auslegung wahlen. - İm letzten Abschnitt, endscheidet wir uns dazu, dass Der Problembereich der Inhaltsgrenzen gehört zum Problem der Vertragsauslegung Eine Kompetz der Gerichte zur Korrektur der unter Einbeziehung von AGB geschlossenen Vertrâge ist abzulehnen. Eine Auslegungsgrundsatz, die Auslegung von AGB habe ohne Berücksichtigung derUmstânde ist abzulehnen.
Keywords: Commercial law; Consumer protection; Contracts; Genel işlem şartları; General transaction conditions; Sözleşmeler; Ticaret hukuku; Tüketicinin korunması

Le contrôle de l'Etat sur les activités privées au Cameroun - Keutcha Tchapnga, Célestin (Aix-Marseille Université, 1992)
Le contrôle que tout Etat exerce sur les activités des personnes physiques et morales de droit privé est une institution politique et juridique fondamentale qui, curieusement, n'a pas retenu l'attention de la doctrine africaine. L'étude de ce contrôle, envisagée dans une triple perspective, (dévoltion du pouvoir de contrôle, objectifs du contrôle, mise en oeuvre du contrôle), recèle, au Cameroun spécialement une signification fondamentale a un triple point de vue : elle illustre les contradictions dont la société est en proie ; elle éclaire ensuite la portée du phénomène de réception des institutions étrangères de contrôle dans le pays ; elle participe enfin à la recherche des solutions adaptées aux multiples problèmes du contrôle. Ces problèmes, qui tiennent essentiellement à l'absence d'une véritable tradition étatique fondée sur la prééminence de l'intérêt général, ne pourront être résolus, dans les directions qui ont pu être mises en relief tout au long de ce travail, qu'à la suite d'une lente et prudente évolution des attitudes politiques et sociales, ainsi que des moeurs administratives.
https://dicames.online/jspui/handle/20.500.12177/1781
Keywords: Activité privée; Contrôle; Etat

La technique des qualifications contractuelles - Henry, Xavier (Université Nancy 2, 1992)
La description de la technique des qualifications contractuelles oblige à établir un inventaire raisonné des procédés d'identification des contrats. La première partie est consacrée à une synthèse des critères de qualification des contrats simples nommés ou pas. Les concepts d'objet ou de cause du contrat ne fournissant pas la notion unitaire indispensable à cette recherche, il leur est préféré un concept synthétique regroupant deux structures de qualification. La structure interne étudiée dans le premier titre correspond à un assemblage dont les éléments sont des obligations reliées entre elles par des liens de nature causale. La structure externe objet du second titre permet de replacer le contrat dans son environnement concret (objet de la prestation), personnel (qualité des parties) ou juridique (groupe de contrats). La seconde partie s'attache à décrire les techniques de combinaison au sein d'un meêm accord d'obligations d'origine diverse, en tenant de distinguer les différents procédés de construction de ces contrats composites et de contribuer à la découverte des principes régissant la détermination de leur régime. Les deux premiers titres sont consacrés aux assemblages qui respectent la nature des éléments combinés en dissociant les intégrations hiérarchisées (obligation accessoire) et égalitaires (contrat mixte), alors que le troisième s'intéresse aux techniques dénaturant les éléments combinés (contrat mixte par fusion d'objet ou d'origine causale).
Keywords: Contrat complexe; Contrats; Droit civil; Droit privé; Formation du contrat; Qualification contractuelle; Qualification du contrat; Responsabilité

Trade and justice - Robe, Jean-Philippe (European University Institute, 1992)
Keywords: Intergovernmental fiscal relations; Justice; Trade